1997
DOI: 10.1080/01688639708403847
|View full text |Cite
|
Sign up to set email alerts
|

Identification of side of seizure onset in temporal lobe epilepsy using memory tests in the context of reading deficits

Abstract: Sixty patients with temporal lobe epilepsy were classified into reading deficient (RD; n = 21) and non-reading deficient (non-RD; n = 39) groups. Selective deficits in verbal or nonverbal memory, consistent with side of seizure onset, were evident in the non-RD patients. Both verbal and nonverbal memory performance were reduced equivalently in individuals with RD, regardless of side of seizure onset. As a result, memory tests that were accurate in identifying side of seizure onset in the non-RD group were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
13
1
Order By: Relevance
“…The control group differed significantly from the TLE group in IQ ( p , .01). The difference in IQ is consistent with the level of intellectual ability reported in previous studies of TLE (e.g., Breier et al, 1997;Camfield et al, 1984;Glosser et al, 1997;Hermann & Wyler, 1988). It is also consistent with the association between early age of onset of recurrent seizures and poorer cognitive functioning.…”
Section: Introductionsupporting
confidence: 87%
“…The control group differed significantly from the TLE group in IQ ( p , .01). The difference in IQ is consistent with the level of intellectual ability reported in previous studies of TLE (e.g., Breier et al, 1997;Camfield et al, 1984;Glosser et al, 1997;Hermann & Wyler, 1988). It is also consistent with the association between early age of onset of recurrent seizures and poorer cognitive functioning.…”
Section: Introductionsupporting
confidence: 87%
“…This is supported by studies suggesting that tests using material that is more difficult to verbalize (e.g, dot locations or random patterns) typically revealed stronger associations between visual memory performance and RTLE or right hippocampus resections [1619] than tests using abstract designs [2022]. Functional neuroimaging studies also support this by indicating that the type of stimuli (e.g., line drawings) often used in visual memory tests are affected by verbal interference paradigms and reflect fMRI activation in verbal areas of the brain[23].…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, there appears to be a lack of sensitivity of line designs to RTLE even when drawing is not required such as on the Visual Spatial Learning Test [22]. A detailed discussion of visual memory in TLE is beyond the focus of this article, however, alternative stimuli with some empirical support includes dot locations on an asymmetrical circle array [19], dot locations on a selective reminding test [16], and faces [20, 51]. Regardless, these and other studies suggest that alternatives to drawing-based should be further explored among epilepsy patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, and Hermann, Seidenberg, Haltiner, and Wyler (1992) found a signi®cant relationship between degree of language impairment and recall performance on a verbal memory 190 MELISSA OGDEN-EPKER AND C. MUNRO CULLUM task. Along these lines, Breier et al (1997) demonstrated that reading abilities in¯uenced verbal / nonverbal lateralization ®ndings, as subjects with impaired reading skills (regardless of side of seizure origin) were correctly classi®ed as left or right TLE at a lower rate and incorrectly classi®ed more often than those subjects without a reading de®cit. Thus, it appears language skills may provide independent lateralizing information, as well as impact performance on verbal memory measures.…”
Section: Discussionmentioning
confidence: 95%